Essentials of statistics - Triola, Mario F. (Boston, Massachusetts : Pearson, 2015)
This book reflects recommendations from the American Statistical Association and its guidelines for assessment and instruction in statistics education (GAISE).
1. Introduction to statistics -- 2. Summarizing and graphing data -- 3. Statistics for describing, exploring, and comparing data -- 4. Probability -- 5. Discrete probability distributions -- 6. Normal probability distributions -- 7. Estimates and sample sizes -- 8. Hypothesis testing -- 9. Inferences from two samples -- 10. Correlation and regression -- 11. Chi-square and analysis of variance.
Includes index.
Keywords: STATISTICS